6(2+y)=5(3+y)

Simple and best practice solution for 6(2+y)=5(3+y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2+y)=5(3+y) equation:


Simplifying
6(2 + y) = 5(3 + y)
(2 * 6 + y * 6) = 5(3 + y)
(12 + 6y) = 5(3 + y)
12 + 6y = (3 * 5 + y * 5)
12 + 6y = (15 + 5y)

Solving
12 + 6y = 15 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
12 + 6y + -5y = 15 + 5y + -5y

Combine like terms: 6y + -5y = 1y
12 + 1y = 15 + 5y + -5y

Combine like terms: 5y + -5y = 0
12 + 1y = 15 + 0
12 + 1y = 15

Add '-12' to each side of the equation.
12 + -12 + 1y = 15 + -12

Combine like terms: 12 + -12 = 0
0 + 1y = 15 + -12
1y = 15 + -12

Combine like terms: 15 + -12 = 3
1y = 3

Divide each side by '1'.
y = 3

Simplifying
y = 3

See similar equations:

| 2x(2)+-3x+-1=0 | | -8(4-5z)+4(7z-10)=0 | | (7i-1/3i)= | | 5p-3=9p-12 | | (10x^2-11x-5)/(2x-3) | | 10x^2-11x-5)/(2x-3) | | 5x^2-8x-67=-2 | | 5p-3=3p-12 | | 7x-32=4 | | b-3/15 | | 3x^2-4=-1 | | -20x^2-25x-6=0 | | 12k+11(3k-5)=0 | | 7z+77=4(z+38) | | 5+2(x+3)=23-4(3x-5) | | 8x-62=26 | | 13=3/4(7x+8) | | p+6.2=10.8 | | 538/270 | | 4(-3a+13)+3(a+4)=0 | | 7z+77=4z+158 | | 8u^2=72 | | 4x/3=3x/2 | | 2x-8(2-x)=19 | | -19+9(4-5X)=0 | | 5ab+3ab-4ab= | | 5z-35=3z+15 | | 4m+6=15answer | | 1+x=1.25 | | n+2=+14-n | | -9(2a+7)-5(4+5a)=0 | | 24x^2+16x+144x=0 |

Equations solver categories